2020
DOI: 10.1016/j.eururo.2020.06.036
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19–related Mortality During the First 60 Days After Kidney Transplantation

Abstract: Patient 2 commenced pembrolizumab 200 mg every 3 wk in November 2016; his PSA was 0.43 mg/l and scans revealed bilateral pelvic nodes, a large pelvic mass (53 mm), and a complex fistula between the rectum and bladder. He received 11 pembrolizumab courses with no immunological toxicity and experienced a partial response. However, pembrolizumab was stopped because of fistula worsening requiring intravenous antibiotics and surgical intervention. He made a full recovery and remains disease-free 40 mo after startin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 5 publications
2
40
1
1
Order By: Relevance
“…Sánchez-Álavarez et al was a report from a national COVID-19 registry across Spain, 12 while Pascual et al and Pérez-Sáez et al reported on subgroups from this registry (those within 60 days of transplantation, and those treated with tocilizumab respectively). 13 , 14 Bell et al and Ravanan et al reported from national transplant registries in Scotland and England respectively, while Manganaro et al reported on from a regional registry in Italy. 11 , 15 , 16 Kates et al reported on data entered to a registry by over 50 transplant centres, almost all from the USA, 10 while Cravedi et al was a report of a consortium registry of 12 transplant centres across USA, Italy and Spain.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sánchez-Álavarez et al was a report from a national COVID-19 registry across Spain, 12 while Pascual et al and Pérez-Sáez et al reported on subgroups from this registry (those within 60 days of transplantation, and those treated with tocilizumab respectively). 13 , 14 Bell et al and Ravanan et al reported from national transplant registries in Scotland and England respectively, while Manganaro et al reported on from a regional registry in Italy. 11 , 15 , 16 Kates et al reported on data entered to a registry by over 50 transplant centres, almost all from the USA, 10 while Cravedi et al was a report of a consortium registry of 12 transplant centres across USA, Italy and Spain.…”
Section: Resultsmentioning
confidence: 99%
“…From left to right, quality items were starred black if they fulfilled pre-defined criteria: selection was starred on representativeness of patients with the exposure of interest (kidney transplant), selection of the non-exposed group, ascertainment of exposure, and demonstration that outcome of interest (death) was not present at start of the study; comparability was starred on the study controlling for the exposure of interest, and any additional factor; outcome was starred on how the outcome was assessed, whether follow-up was long enough for the outcome to occur, and whether loss to follow-up was adequate enough to be unlikely to introduce bias. Study design Selection Comparability Outcome Manganaro et al 16 Single-centre case series ☆☆★★ ☆☆ ☆☆☆ Boyarksy et al 18 Cross-sectional national survey ☆☆☆★ ☆☆ ☆☆☆ Pereira et al 21 Two-centre case series ★☆★★ ☆☆ ★☆☆ Sánchez-Álvarez et al 12 National registry cohort ★★☆★ ★☆ ☆★☆ Vistoli et al 19 Cross-sectional national survey ★☆☆★ ☆☆ ☆☆☆ Rodriguez-Cubillo et al 23 Single-centre case series ★☆★★ ☆☆ ★★★ Pascual et al 13 National registry case series ★☆★★ ☆☆ ★☆☆ Chen et al 27 Single-centre case series ★☆★★ ☆☆ ★★★ Mehta et al 28 Single-centre case series ★☆★★ ☆☆ ★★★ Bossini et al 25 Multi-centre case series ★☆★★ ☆☆ ★★★ Cravedi ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…None of our patients has been infected by SARS-CoV-2 during hospitalization or follow-up, supporting the preliminary data that suggest a low risk of acquiring the viral infection by transplanted patients, with a clinical course not different from that of nontransplant individuals [ 4 , 12 14 ]. However, the affected patients seem to have a higher risk of becoming seriously ill and have an increased rate of mortality, especially in older patients [ 11 , 12 , 15 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even our only preemptive patient decided to delay the transplantation till the end of the lockdown, accepting the probability of starting dialysis treatment. The temporary suspension of elective living donor transplantation is supported by the most recent recommendations worldwide [ 5 , 15 , 25 27 ].…”
Section: Discussionmentioning
confidence: 99%